Heat and carbon monoxide exposure: Is two better than one? - Webb, K. L.; González-Alonso, J. (Experimental Physiology, 2024)
In this issue of Experimental Physiology, DiMarco et al. provide insight into two acute interventions that elicit haematological adaptation with potential ergogenic effects (DiMarco et al., 2024). First, carbon monoxide exposure reduces arterial blood oxygenation, impairing oxygen delivery to the visceral organs such as the kidneys with little renal blood flow compensation (Schmidt et al., 2020). In response, the kidney detects a reduction in oxygen delivery and stimulates the production of EPO, increasing haemoglobin mass in compensation (Montero & Lundby, 2019). Through differing mechanisms, acute heat exposure is generally considered to reduce renal blood flow, lowering oxygen delivery and thus evoking a similar EPO response in compensation (Oberholzer et al., 2019). The potential utility of carbon monoxide and heat exposure is to increase the total amount of red blood cells and haemoglobin mass, which have been positively associated with a greater aerobic capacity and athletic performance (Schmidt & Prommer, 2010). Both methodologies elicit haematological responses that have been studied previously, but the novelty of DiMarco et al.`s work stems from (1) evaluating a hypothetical potentiating effect of performing acute carbon monoxide exposure and passive heating concomitantly, and (2) investigating potential sex differences yet to be addressed.